Question
upstudy study bank question image url

1365. a) \( 3^{x-3^{x+3}=-78} \) б) \( 5^{2 x-1}-5^{2 x-3}=4,8 \)

Ask by Hobbs Brewer. in Uzbekistan
Feb 03,2025

Real Tutor Solution

Tutor-Verified Answer

Answer

**Ответ:** a) \( x = 1 \) b) \( x = 1 \)

Solution

### Решение задачи 1365 #### a) \( 3^{x} - 3^{x+3} = -78 \) 1. **Приведём уравнение к удобному виду:** \[ 3^{x} - 3^{x+3} = -78 \] 2. **Вынесем общий множитель \( 3^{x} \):** \[ 3^{x} (1 - 3^{3}) = -78 \] \[ 3^{x} (1 - 27) = -78 \] \[ 3^{x} \cdot (-26) = -78 \] 3. **Разделим обе стороны на \(-26\):** \[ 3^{x} = \frac{-78}{-26} = 3 \] 4. **Решаем уравнение \( 3^{x} = 3 \):** \[ x = 1 \] **Ответ:** \( x = 1 \) #### б) \( 5^{2x-1} - 5^{2x-3} = 4,8 \) 1. **Приведём уравнение к удобному виду:** \[ 5^{2x-1} - 5^{2x-3} = 4,8 \] 2. **Обозначим \( y = 5^{2x-3} \). Тогда \( 5^{2x-1} = 5^{2x-3} \cdot 5^{2} = y \cdot 25 \):** \[ 25y - y = 4,8 \] \[ 24y = 4,8 \] \[ y = \frac{4,8}{24} = 0,2 \] 3. **Возвращаемся к исходному обозначению:** \[ y = 5^{2x-3} = 0,2 \] \[ 5^{2x-3} = \frac{1}{5} = 5^{-1} \] 4. **Приравниваем показатели:** \[ 2x - 3 = -1 \] \[ 2x = 2 \] \[ x = 1 \] **Ответ:** \( x = 1 \) --- Оба уравнения имеют решение \( x = 1 \).

Reviewed and approved by the UpStudy tutoring team

error msg
Explain
Simplify this solution

Beyond the Answer

First, let's tackle the equation \( 3^{x} - 3^{x+3} = -78 \). We can rewrite \( 3^{x+3} \) as \( 3^{x} \cdot 3^{3} = 27 \cdot 3^{x} \). Thus, the equation becomes: \[ 3^{x} - 27 \cdot 3^{x} = -78 \] This simplifies to: \[ -26 \cdot 3^{x} = -78 \] Dividing both sides by -26, we find: \[ 3^{x} = 3 \] Taking logarithms or recognizing the powers, we conclude: \[ x = 1 \] Now, for the second equation \( 5^{2x-1} - 5^{2x-3} = 4.8 \), let's make a substitution. Let \( y = 5^{2x} \). Then, we can express the equation as: \[ \frac{y}{5} - \frac{y}{125} = 4.8 \] Multiplying through by 125 to eliminate the fractions gives: \[ 25y - y = 600 \] Simplifying further, we find: \[ 24y = 600 \] From this, we get: \[ y = 25 \] Recall our substitution \( y = 5^{2x} = 25 \). This means: \[ 5^{2x} = 5^{2} \] So, \[ 2x = 2 \] and consequently: \[ x = 1 \] Thus, the solutions are: a) \( x = 1 \) b) \( x = 1 \)

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy